How the Distance Learning can be a Solution during the Covid-19 Pandemic - Dedi Riyan Rizaldi; Ziadatul Fatimah (International Journal of Asian Education, 2020)
This study investigates the implemented distance learning system from home as the Indonesian government's policy slogans during the COVID-19 pandemic. The use of various distance learning system platforms currently available adjusted to the learning process's needs to carry out provides a solution to break the chain of spreading COVID-19 in Indonesia. The research using a literature review that consists of four stages, namely (1) Identification of research topic keywords, (2) identification of abstracts from various literature sources, (3) making notes of identification results, and (4) link notes periodically. Based on the results and discussion, distance learning is an effective solution to continuing the learning process during the COVID-19 pandemic, when it does not allow direct learning in the classroom. However, to increase distance learning success, various considerations are needed, such as infrastructure, teacher and student readiness, and expected learning outcomes. Therefore, teachers as an essential factor in the achievement of the learning process, especially during the COVID-19 pandemic, must be able to create and provide usefully and not dull learning conditions, one of which is by trying to use various learning models platforms such as Zoom Cloud Meeting, Google Forms, Jitsi Meet App, Whatsapp Groups and more.